Certain issues of conducting covert investigative (detective) actions in criminal proceedings on economy-related crimes - Repchonok, A. Yu.; Репчонок, А. Ю. (Visegrad journal on human rights. – 2022. – № 4. – P. 139-144, 2022)
Досліджено окремі питання щодо проведення негласних слідчих (розшукових) дій у кримінальних провадженнях про злочини, пов’язані з економікою, з акцентом на особливості моніторингу банківських рахунків та отримання інформації з електронних комунікаційних мереж. Визначено, що правове регулювання такої негласної слідчої (розшукової) дії, як спостереження банківських рахунків динамічно розвивається. Доповнення КПК статтею 269-1 України та наступні зміни до нього порушили багато проблемних питань, які потребують розгляду. Моніторинг банківського рахунку, як і будь-яка інша процесуальна дія, повинна детально врегульовано в КПК України з дотриманням принципу правової визначеності. Порядок передачі інформації про проведені операції за рахунками в банку з банку до правоохоронного органу в нинішньому режимі має бути більш детально врегульовано . Наголошено, що проведення слідчі (розшукові) дій у вигляді отримання інформації з засобів електронного зв'язку мережі є одним із найефективніших засобів виявлення та розслідування економічних злочинів. Отримання відповідних доказів шляхом цієї негласної дії є досить ефективним процесуальним засобом, який вимагає чіткого дотримання законодавчих вимог і ретельно виваженої тактики.

The article examines certain issues related to covert investigative (detective) actions in criminal proceedings on economy-related crimes, with a focus on the specifics of monitoring bank accounts and obtaining information from electronic communication networks. It has been determined that the legal regulation of such covert investigative (detective) action as monitoring of bank accounts is undergoing dynamic development. The addition of Article 269-1 to the CPC of Ukraine and subsequent amendments to it have raised many problematic issues that need to be further addressed. Bank account monitoring, as well as any other procedural action, should be regulated in detail in the CPC of Ukraine in compliance with the principle of legal certainty. In particular, the right of investigators (detectives) of any pre-trial investigation body to monitor bank accounts in criminal proceedings should be provided for at the legislative level. In addition, the procedure of transferring the information on transactions carried out on bank accounts from the bank to the law enforcement agency in the current mode should be regulated in more detail and the issue of joint control over banking transactions in the online mode, through access to the electronic information space of the bank, should be resolved at the regulatory level. Given the dynamic development of communication and information technologies, conducting covert investigative (detective) actions in the form of information obtaining from electronic communication networks is one of the most effective means of detecting and investigating economic crimes. Obtaining relevant evidence through this covert action is a fairly effective procedural tool that requires strict compliance with legal requirements and carefully considered tactics.

Исследованы отдельные вопросы проведения негласных следственных (розыскных) действий в уголовных производствах о преступлениях, связанных с экономикой, с акцентом на особенности мониторинга банковских счетов и получения информации из электронных коммуникационных сетей.
Repchonok, A. Certain issues of conducting covert investigative (detective) actions in criminal proceedings on economy-related crimes / Repchonok Andrii // Visegrad journal on human rights. – 2022. – № 4. – P. 139-144.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; негласні слідчі (розшукові) дії; secret investigative (research) actions; негласные следственные (розыскные) действия; економічна злочинність; economic crime; экономическая преступность; отримання інформації з електронних мереж зв'язку; obtaining of information from electronic communication networks; получение информации из электронных сетей связи; моніторинг банківських рахунків; monitoring of bank accounts; мониторинг банковских счетов